Athletes have more susceptibility to oxidative stress: Truth or myth? A study in swimmers - Matias, C. N.; Bicho, M.; Laires, M. J.; Monteiro, C. P. (Science & Sports, 2020)
Aims: Exercise is associated with accelerated reactive oxygen species (ROS) generation and stimulation of the antioxidant defences (AD). In high intensity exercise ROS production may overwhelm the AD and induce adverse effects on health and performance. We aim to investigate the redox balance of adult-competitive swimmers against recreational exercise practitioners. Methods: Fifteen high-competition male swimmers (S) and 16 active men (AM), all aged between 18-25 years, participated in the study. Venous blood was collected at rest in the morning to assess oxidative and muscle damage markers, antioxidant enzymatic activities in erythrocytes, and non-enzymatic antioxidants in plasma. All parameters were assessed by photometry with the exception of thiobarbituric acid reactive substances (TBARS), assessed by fluorimetry. Bivariate correlations were performed to investigate the association between all redox balance markers. Partial correlation analysis was conducted to control for the exercise level. Results: Differences between groups were observed in red blood cells peroxidation (RBCPx-S: 39.2±4.8; AM: 46.3±9.5%) and in meta-hemoglobin reductase (RmHb - S: 7.5±2.1; AM: 9.1±2.3µmol/min.gHb), with S presenting lower mean values (P<0.05). Controlling for the exercise level, adrenaline oxidase (AdOx) was inversely correlated with carotenoids (R=-0.596; P=0.001) and directly with creatine kinase (CK) (R=0.413; P=0.045) and with TBARS (R=0.532; P=0.005); RBCPx was inversely correlated with acid phosphatase (ACP1) (R=-0.392; P=0.048) and directly with glutathione reductase (GR) (R=0.524; P=0.006); GR was inversely correlated with TBARS (R=-0.404; P=0.041); VitE was directly correlated with Carotenoids (R=0.723; P=0.001) and inversely with TBARS (R=0.543; P=0.004). Therefore: AD are effective at controlling ROS; VitE and carotenoids are important protective lipid antioxidants; higher TBARS may be associated to the stimulation of GR activity; muscle leakages associated to the AdOx activity which may result from ion leakage, intravascular hemolysis or inflammation. Conclusion: Our results suggest that competitive swimmers are not at higher risk of oxidative damage than recreational exercise practitioners.